Negative epistasis between α+ thalassaemia and sickle cell trait can explain interpopulation variation in South Asia. - Penman, B; Habib, S; Kanchan, K; Gupta, S (2011)
Recent studies in Kenya and Ghana have shown that individuals who inherit two malaria-protective genetic disorders of haemoglobin-α(+) thalassaemia and sickle cell trait-experience a much lower level of malaria protection than those who inherit sickle cell trait alone. We have previously demonstrated that this can limit the frequency of α(+) thalassaemia in a population in which sickle cell is present, which may account for the frequency of α(+) thalassaemia in sub-Saharan Africa not exceeding 50%. Here we consider the relationship between α(+) thalassaemia and sickle cell in South Asian populations, and show that very high levels of α(+) thalassaemia combined with varying levels of malaria selection can explain why sickle cell has penetrated certain South Asian populations but not others.